Pollution of the Opamayo river by the municipal slaughterhouse in the town of Pampas-Tayacaja, 2023 - Chavarría Marquez, Esmila Yeime (2023)
The presence of fecal coliforms in the Opamayo River and its effects on the public health of the population of Pampas Tayacaja. The methodology used is the quantitative method; The study population includes all the houses around the Opamayo River, affected by the contamination of the river by the mentioned municipal slaughterhouse; for which surveys, interviews and the experimental method were used. The results show that the identified diseases are mostly digestive, respiratory and infectious; Likewise, through a laboratory study, the river water sample resulted as a positive sample for fecal coliforms, considering an indication of contamination and potential presence of bacteria that cause diseases. The majority of the population (66.75%) uses water for agriculture or livestock, the identified diseases are mostly gastrointestinal and digestive with 83.3%. In addition, these consequences are suffered mostly by the female population with 56.7%, and 60% of the population mentions that they do not receive help from the municipality and hospital of Pampas. It was concluded that there is great concern on the part of the population residing around the Opamayo River since they show the effects of the contamination of the river by the municipal slaughterhouse on their health and there are no immediate actions on the part of the authorities. On the other hand, it is determined that there is a presence of fecal coliforms in the river, through a laboratory study.